2022
DOI: 10.1055/s-0041-1740957
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the IMA Recipient Site for DIEP Flap Surgery: A New Model for Dynamic Microsurgery Simulation with Real-Time Respiration and a Pilot Study

Abstract: Background Breast reconstruction (BR) using autologous free flaps has been shown to have numerous psychosocial and quality-of-life benefits. Unfortunately, the microsurgical learning curve is quite steep due to some unique operative challenges. Currently, there is no realistic simulation model that captures real-life respiratory excursion and the depth of internal mammary vessels within the compact recipient site. The purpose of this study was to delineate intraoperative measurements of depth and motion, descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In our simulator, the inner baffling rods imitate deep and narrow diastema such as the oral cavity, intercostal space, and intracranial space, which trains novices to handle microsurgical instruments dexterously and rotate their wrists flexibly. Based on our clinical experience and literature report, 16 we set the training height of the inner baffling rods to be 5 cm, which is deep enough to cover most cavities in microsurgery. A study reported by Chauhan et al also noticed the importance of practicing vessel anastomosis in a deep cavity; however, the study only used single constrained factor and synthetic vessel material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our simulator, the inner baffling rods imitate deep and narrow diastema such as the oral cavity, intercostal space, and intracranial space, which trains novices to handle microsurgical instruments dexterously and rotate their wrists flexibly. Based on our clinical experience and literature report, 16 we set the training height of the inner baffling rods to be 5 cm, which is deep enough to cover most cavities in microsurgery. A study reported by Chauhan et al also noticed the importance of practicing vessel anastomosis in a deep cavity; however, the study only used single constrained factor and synthetic vessel material.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the model was modified from a Medical SimMan, the cost was really high. 17 Furthermore, in our device, the combination of these artificial obstacles enhances the degree of training difficulty while replicating authentic microsurgical scenarios as accurately as possible. This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziolkowski et al recently published a pilot study of a novel, fully synthetic, DIEP flap IMA anastomosis surgical simulator. 25 This model focused on providing authentic simulation of chest excursion that occurs during natural breathing of a patient while completing the surgical anastomosis of this procedure. The authors demonstrated residents had an increase in confidence performing anastomoses after practice on the simulator, highlighting the importance of surgical simulation in the acquisition of the specific skills of insetting a DIEP flap and improving confidence prior to the operating theater.…”
Section: Discussionmentioning
confidence: 99%